If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -59 = -3 + -7x Solving -59 = -3 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -59 + 7x = -3 + -7x + 7x Combine like terms: -7x + 7x = 0 -59 + 7x = -3 + 0 -59 + 7x = -3 Add '59' to each side of the equation. -59 + 59 + 7x = -3 + 59 Combine like terms: -59 + 59 = 0 0 + 7x = -3 + 59 7x = -3 + 59 Combine like terms: -3 + 59 = 56 7x = 56 Divide each side by '7'. x = 8 Simplifying x = 8
| 0.12x+0.06(3-x)=0.09(x-1) | | 1.1(5x-7)+3.6=0.2(9-2x) | | 2x(m+5)=40 | | .05x+1.5-.10x=1.15 | | 0.8x(4x-3)+0.3(7-10x)=-0.2 | | 4x-3y=-32 | | 3(x+10)-3=81-3x | | f(x)=((4))/((3x^2-5x^4)^4) | | 9x-4=158 | | [7x+4]+9=4 | | 0.5x-0.4x(3x+8)=0.3 | | (4)/((3x^2)-(5x^4))^4 | | 3y+2(y-4)=2 | | (11((x-7)/2)^2)-20=101 | | 15/9=8/5 | | (4)/((3x^2-5x^4)^4) | | 3x+13=90 | | ((4)/((3x^2-5x^4)^4)) | | f(x)=(4)/(3x^2-5x^4)^4 | | 9x-4=39.5 | | (4)/(3x^2-5x^4)^4 | | -10-m=-70 | | 36=(90/360)*x*x | | 4a-14=2a | | (4/5)-(2x/3)=(3/10) | | (x-3)(x+1)=x*-11 | | n^3-64/125 | | 3m-1-36=11 | | 3.16x+x= | | (X-3)(x+1)=x*11 | | 5n-7=32 | | m-39+93-13=36 |